Medicine Management For Nurses. - Barber, Paul (McGraw-Hill Education, 2013)
This essential case book is aimed at nurses studying pharmacology/medicine management at pre-registration level as well as qualified nurses studying Non Medical Prescribing. The cases cover a variety of conditions helping students to learn what to do in many types of scenarios.